Fate and behavior of inorganic constituents of RDF in a two stage fluid bed-plasma gasification plant. (15th June 2015) - Materazzi, Massimiliano; Lettieri, Paola; Mazzei, Luca; Taylor, Richard; Chapman, Chris
Highlights: An examination of residues from a two-stage waste thermal treatment is presented. Sulphur and chlorine are partially retained in the first stage. Alkali metals are partially inactivated by reactions with the mineral matter of RDF. 90% of ash-type components in RDF are recovered as a stable vitrified product. Abstract: To accelerate progress in the industrial use of RDF as an alternative fuel in gasification plants, the problems associated with hazardous solid residues and ash deposition must be resolved. The practical approach to reduce these problems must be aimed at preventing the accumulation of fly ash/condensable vapours on heat transfer surface areas while minimising the amount of residual materials that have to be treated before the disposal. One such approach is adopted in an advanced two-stage thermal process which incorporates a plasma processing stage for conditioning the gas generated from a primary waste gasification unit, primarily for the treatment of household and industrial wastes. This paper presents a comprehensive examination of ashes sampled under different operational conditions and in different locations of a two-stage fluid bed-plasma demonstration plant. A demonstration test miming the normal commercial operation was conducted over 44 h of operation with RDF from a standard UK municipal solid waste. The results are presented according to solid samples composition, gas composition, and further specific data (e.g., enrichment factor, XRD analysis, leaching test, etc.). An investigation on pollutant removal from the hot syngas, focusing on the partitioning and chemistry of sulphur and chlorine along with other relevant components, is also carried out. Experimental trials revealed a reduced extent of alkali and metals availability in the gas phase, i.e. a minor deposit forming potential into downstream equipment. From 85% to 91% of the fly ash was captured and vitrified within the plasma converter and made non-leachable with respect to non-volatile heavy metals, allowing for near complete landfill diversion.